2014
DOI: 10.1016/j.bbmt.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Validation of National Institutes of Health Global Scoring System for Chronic Graft-Versus-Host Disease (GVHD) According to Overall and GVHD-Specific Survival

Abstract: A new severity grading system for graft-versus-host disease (GVHD) was established by the National Institutes of Health (NIH) consensus criteria (NCC). However, its prognostic value still needs to be validated. Four hundred twenty-five consecutive patients who survived beyond 100 days after allogeneic stem cell transplantation were reviewed and reclassified using NCC. GVHD-specific survival (GSS) and cumulative incidence of relapse were compared according to the NIH global score at the onset and peak of chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 18 publications
4
25
1
2
Order By: Relevance
“…Furthermore, patients with severe cGVHD had a significantly higher TRM compared with patients with mild or moderate cGVHD. Our data are in accordance with recent studies that reported a correlation between cGVHD severity and outcome after allo-SCT and it is suggested that patients with severe cGVHD represent an unfavorable subgroup [3,11,18,27,38,55,56,[58][59][60][61][62]66,67].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, patients with severe cGVHD had a significantly higher TRM compared with patients with mild or moderate cGVHD. Our data are in accordance with recent studies that reported a correlation between cGVHD severity and outcome after allo-SCT and it is suggested that patients with severe cGVHD represent an unfavorable subgroup [3,11,18,27,38,55,56,[58][59][60][61][62]66,67].…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with recently published studies, we found a significantly lower incidence of relapse in patients with compared with patients without cGVHD and this might be caused by a graft-versus-leukemia effect similar to that of aGVHD [2,11,18,27,55,60,[71][72][73]. Patients with severe (but not with mild or moderate) cGVHD had a significantly lower relapse rate compared with patients without cGVHD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, this approach enables more consistent assessment and treatment of cGvHD and improved evaluation of outcomes. The system's prognostic value has been validated in an independent adult cohort in whom a severe score was associated with significantly increased risk of death from cGvHD or causes related to its treatment,32 but has not been confirmed yet in children.…”
Section: Chronic Gvhdmentioning
confidence: 99%
“…Il lui est également demandé d'évaluer ses symptômes dans différents organes (annexe 3) et/ou de rapporter sa qualité de vie à l'aide d'un questionnaire standardisé (annexe 4). Il a été démontré que le score de sévérité au diagnostic de la GvHc [15] et la réponse au traitement non confirmé par Inamoto et al [16], ont une valeur prédictive de la possibilité de sevrer les patients du traitement immunosuppresseur et de leur survie. Il est parfois très difficile, notamment pour les formes scléro-dermiques, de distinguer une GvHc active qui nécessite la poursuite du traitement immunosuppresseur de séquelles fixées d'une GvHc qui n'est plus du tout active et pour laquelle le traitement pourrait être arrêté.…”
Section: Comment éValuer La Réponse ?unclassified